The Problem of Using Conservative or Liberal Typography in the Printed Graphic Design - Waseif, Ahmed; Waseif, Mohammed; Omar, Mohamed; Abd el Latief, Mahmoud; Abd el Qader, Wael (Dirasat: Human and Social Sciences, 2020)
The use of "typography" today is increasingly recognized through multiple means of visual communication as the most influential "visual language" in the recipient through language clarity, readability and design aesthetics. On the other hand, it encourages the recipient to respond in a variety of responses corresponding to marketing strategy or to influence the quality of the environment, people's lives, cultures and needs more effectively. This research is a problematic study/modality of using "typography" in its Styles ... Whether the Conservative with the solid traditions or the Contemporary with the New Trends in Graphic Design fields of such as: - Corporate Design (logos and branding), Editorial Design (Magazines, Newspapers and Books), web design or Campaigns poster design.